Emerging resistance in Staphylococcus epidermidis during dalbavancin exposure: a case report and in vitro analysis of isolates from prosthetic joint infections. (6th January 2023) - Al Janabi, Jasmina; Tevell, Staffan; Sieber, Raphael Niklaus; Stegger, Marc; Söderquist, Bo
Abstract: Background: Dalbavancin, a semisynthetic lipoglycopeptide with exceptionally long half-life and Gram-positive spectrum, is an attractive option for infections requiring prolonged therapy, including prosthetic joint infections (PJIs). Objectives: To investigate the prevalence of reduced susceptibility to dalbavancin in a strain collection of Staphylococcus epidermidis from PJIs, and to investigate genomic variation in isolates with reduced susceptibility selected during growth under dalbavancin exposure. Methods: MIC determination was performed on S. epidermidis isolates from a strain collection ( n  = 64) and from one patient with emerging resistance during treatment ( n  = 4). These isolates were subsequently cultured on dalbavancin-containing agar and evaluated at 48 h; MIC determination was repeated if phenotypical heterogeneity was detected during growth. Population analysis profile (PAP-AUC) was performed in isolates where a  ≥ 2-fold increase in MIC was detected, together with corresponding parental isolates ( n  = 21). Finally, WGS was performed. Results: All strains grew at 48 h on agar containing 0.125 mg/L dalbavancin. PAP-AUC demonstrated significant differences between parental and derived strains in four of the eight analysed groups. An amino acid change in the walK gene coinciding with emergence of phenotypic resistance was detected in the patient isolates, whereas no alterations were found in this region in the in vitro derived strains. Conclusions: Exposure to dalbavancin may lead to reduced susceptibility to dalbavancin through either selection of pre-existing subpopulations, epigenetic changes or spontaneous mutations during antibiotic exposure. Source control combined with adequate antibiotic concentrations may be important to prevent emerging reduced susceptibility during dalbavancin treatment.